Structural and thermophysical properties characterization of continuously reinforced cast Al matrix composite - Brian Gordon; Natalia Sobczak; Malorzata Warmuzek (China Foundry, 2010)
In this work the process of manufacturing a continuously reinforced cast Al matrix composite and its properties are presented. The described technology permits obtaining a structural material of competitive properties compared to either heat treatable aluminum alloys or polymer composites for several types of applications. The examined thermophysical properties and structural characterization, including material anisotropy, coupled with the results of previous measurements of the mechanical properties of both Al2O3 reinforcing filaments and metallic prepregs have proven the high quality of this material and the possibility of its operation under special loading modes and environmental conditions. Microscopic examinations (LM, SEM) were carried out to reveal the range of morphological homogeneity of the microstructure, the anisotropy of the filament band distribution, and simultaneously the adhesive behavior of the metal/fiber interface. The 3D morphology of the chosen microstructure components was revealed by computed tomography. The obtained results indicate that special properties of the examined prepreg materials have been strongly influenced, on the one hand, by the geometry of its internal microstructure, i.e. spatial distribution and volume fraction of the Al2O3 reinforcing filaments and, on the other hand, by a very good compatibility obtained between the individual metal prepreg components.